Accurate Analysis of Multi-Mode Interferometric Optical Fiber Sensor - Lijun Li; Congying Jia; Qian Ma; Tianzong Xu (Photonic Sensors)
Abstract In view of the problem that the sensing characteristics of the multi-mode interferometric fiber sensors cannot be accurately analyzed, an analysis method based on the fast Fourier transform (FFT) and inverse fast Fourier transform (IFFT) is proposed and demonstrated theoretically and experimentally. The suitabilities of the rectangular window function with the narrow main lobe (high spectrum resolution) and low side lobe (high main mode energy leakage) and the Hanning window function with the wide main lobe (low spectrum resolution) and high side lobe (high energy concentration) in this kind of sensor analysis are discussed, respectively. This method can not only realize the sensing performance analysis of the various modes, but also overcome the inconsistency of the different interference wavelength (dip) sensing characteristics in the conventional analysis methods. At the same time, this method is also beneficial to solve the repetitive problem of such sensors.